Comparative Analysis of Preoperative Ultrasonography Reports with Intraoperative Findings in Cholelithiasis - Shrestha, Mukunda Singh; Pant, Sujit; Rayamajhi, Bikash Bahadur; Khadka, Milan; Khadka, Ramesh; Lamsal, Sudesh (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Cholecystectomy is a popular surgical intervention for cholelithiasis. Preoperative abdominal ultrasonography is helpful for diagnosis and prediction of possible surgical complications. This research was planned to correlate the preoperative abdominal ultrasonography findings with intraoperative findings and complications. Methods: A hospital based retrospective study was conducted among 300 patients visiting Surgery Department and Department of Radiology of Shree Birendra Hospital, Kathmandu, Nepal. Descriptive statistics was used to present the comparative analysis of preoperative ultrasonography reports with intraoperative surgical findings in cholecystectomy. Results: Total 300 participants were who were diagnosed by ultrasonography and underwent cholecystectomy were included in the study. Complications were reported among 110 subjects with adhesions in 20%, mucoceles in 7.3%, empyema in 8%, and impacted stone in 1.3.%. Out of 75 patients in which preoperative USG reports showed increased GB wall thickness, 17 (22.6%) had adhesions, 10 had mucoceles (1.3%), eight had empyema (10.6%), one had impacted stone (1.3%) and three had hemorrhage (4%). Conclusion: The most reliable preoperative abdominal ultrasonography indicators of a challenging cholecystectomy are gall bladder wall thickness, impacted gall stones, adhesion and hemorrhage.